A single centre cohort experience with a new once daily antiretroviral drug. Issue 967 (5th May 2006) - Stebbing, J; Bower, M; Holmes, P; Gazzard, B; Nelson, M
Abstract : Background: Atazanavir, an azadipeptide protease inhibitor (PI) with once daily dosing, a lack of insulin resistance, lipid increase, and gastrointestinal toxicities, is approved in combination with other antiretrovirals for the treatment of patients infected with HIV. Unboosted atazanavir is also used in highly active antiretroviral therapy (HAART) naive patients. Methods: The study prospectively followed up an established cohort of patients who received atazanavir, and for whom one year of follow up data were available. Results: It was found that use of atazanavir in intent to treat and on treatment analyses, maintained and led to virological suppression and increases in CD4 count in both PI naive and experienced patients. Virological failure occurred in 7% of patients and the main toxicity was hyperbilirubinaemia, which led to treatment withdrawal in 2%. Its efficacy and safety profile was similar to that seen in previous randomised studies investigating its use. Conclusions: These data should provide reassurance for clinicians wishing to introduce a new antiretroviral into an established cohort.